The MPIfR-MeerKAT galactic plane survey - I. System set-up and early results - Voraganti Padmanabh, Prajwal; Barr, E D; Sridhar, S S; Rugel, M R; Damas-Segovia, A; Jacob, A M; Balakrishnan, V; Berezina, Marina; Bernadich, M C; Brunthaler, A; Champion, D J; Freire, P C C; et al. (Monthly notices of the Royal Astronomical Society, 2023)
Galactic plane radio surveys play a key role in improving our understanding of a wide range of astrophysical phenomena. Performing such a survey using the latest interferometric telescopes produces large data rates necessitating a shift towards fully or quasi-real-time data analysis with data being stored for only the time required to process them. We present here the overview and set-up for the 3000-h Max-Planck-Institut für Radioastronomie (MPIfR)-MeerKAT Galactic Plane Survey (MMGPS). The survey is unique by operating in a commensal mode, addressing key science objectives of the survey including the discovery of new pulsars and transients and studies of Galactic magnetism, the interstellar medium and star formation rates. We explain the strategy coupled with the necessary hardware and software infrastructure needed for data reduction in the imaging, spectral, and time domains. We have so far discovered 78 new pulsars including 17 confirmed binary systems of which two are potential double neutron star systems. We have also developed an imaging pipeline sensitive to the order of a few tens of micro-Jansky ($μ{\rm Jy}$) with a spatial resolution of a few arcseconds. Further science operations with an in-house built S-band receiver operating between 1.7 and 3.5 GHz are about to commence. Early spectral line commissioning observations conducted at S-band, targeting transitions of the key molecular gas tracer CH at 3.3 GHz already illustrate the spectroscopic capabilities of this instrument. These results lay a strong foundation for future surveys with telescopes like the Square Kilometre Array (SKA).
Veröffentlicht: 22. Juni 2023
Gesehen am 10.10.2023